Reading strategies effect on reading comprehension performance of ESL learners - Chiam, Kee Swan; Wong, Su Luan; Mohd Ayub, Ahmad Fauzi; Hussin, Habsah (Human Resource Management Academic Research Society, 2018)
The purpose of this study was to discover the relative effectiveness of different types of reading strategies on measures of reading comprehension performance for students with different learning styles. Students were separated into four learning style groups (active, sensitive, visual and sequential) based on their scores on the Index of Learning Styles (ILS) questionnaire. The results indicated that students with varying learning styles responded differently to the reading strategies tested in the study. Active learners performed better than other groups when using the keyword and question and answer strategy but performed significantly worse than other groups with the rereading strategy. Sensitive and sequential learners on the other hand performed better than other groups with the rereading strategy. Visual learners did well with the keyword strategy.Of the strategies tested, only the keyword strategy showed consistently positive results for all learning style groups. Each group scored higher on the keyword condition than on the control condition. Hence use of the keyword strategy is highly recommended in classroom environments and incorporating the keywords into texts to make texts easier to understand is a viable method for improving comprehension. The question and answer strategy should be used with caution as it results in sub-par comprehension for learning styles other than the active learning style. Similarly the rereading strategy which works well for sensitive and sequential learners should also be used only for these learners as it confuses active learners. In a nutshell, a student’s learning preference will influence the way information is processed and thus selecting and using appropriate reading strategies is essential to ensure the best possible results.